Devoted in death [compact disc, unabridged] - Robb, J. D., 1950- (Robb, J. D., 1950- In death novel., 2015)
Eve Dallas, aided by Roarke and her team, investigates clues surrounding a murder of unusual brutality before pursuing a woman and her ex-con boyfriend who have developed a taste for extreme violence.